2010
DOI: 10.1007/s10342-010-0413-0
|View full text |Cite
|
Sign up to set email alerts
|

Does tree seedling growth and survival require weeding of Himalayan balsam (Impatiens glandulifera)?

Abstract: The effect of Himalayan balsam (Impatiens glandulifera) on survival and growth of naturally regenerated silver birch (Betula pendula) and planted Norway spruce (Picea abies) and silver fir (Abies alba) seedlings was studied in a weeding experiment over 3 years. Three different treatments were applied: control, mowing, and hand weeding by pulling out the entire plant. There were no consistent treatment effects on height and diameter of the tree seedlings. The coverage of Rubus fruticosus had a negative impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
(33 reference statements)
0
12
0
1
Order By: Relevance
“…However, Maule et al (2000) showed that in the UK I. glandulifera could successfully compete with native plants, including tree seedlings with the potential to inhibit the regeneration cycle of woodlands. This was not the case, in Germany, Ammer et al (2011), found no impact of I. glandulifera on established tree seedlings.…”
Section: Ecological Impactsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, Maule et al (2000) showed that in the UK I. glandulifera could successfully compete with native plants, including tree seedlings with the potential to inhibit the regeneration cycle of woodlands. This was not the case, in Germany, Ammer et al (2011), found no impact of I. glandulifera on established tree seedlings.…”
Section: Ecological Impactsmentioning
confidence: 88%
“…This was not the case, in Germany, Ammer et al . (), found no impact of I. glandulifera on established tree seedlings.…”
Section: Ecological Impactsmentioning
confidence: 89%
“…In contrast, other studies did not find such negative effects. Thus, seed germination [ 33 ], and forest recruitment were not restricted in invaded forest sites [ 34 ]. These varied outcomes may be caused by context-dependencies, because all these studies were conducted with different settings regarding study conditions, target plants, their developmental stages and the parts of I .…”
Section: Introductionmentioning
confidence: 99%
“…Dennoch wird in der aktuellen Forschung parallel dazu diskutiert, ob die Bedeutung von Impatiens glandulifera Royle nicht überschätzt wird. So wird beispielsweise argumentiert, dass das Indische Springkraut lediglich eine freie ökologische Nische innerhalb der Auenbestände besetzen würde oder maximal in Konkurrenz zu anderen dominanten Nitrophyten wie der Großen Brennnessel (Urtica dioica) treten würde (Ammer et al, 2011;Hejda & Pyšek, 2006;Hejda et al, 2009;Kowarik, 2003).…”
Section: Bestimmung Der Bedeutung Der Konkurrenz Von Neophytenunclassified